Best cubature formulas for some classes of continuous functions of two variables - Polyakov, O. V.; Polyakova, N. O. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
The exact value of the error of a cubature formula is determined for some classes of continuous functions of two variables defined by strictly monotone moduli of continuity.